2010
DOI: 10.1016/j.juro.2010.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Adenocarcinoma of the Prostate: Increased Mortality Risk and Decreased Serum Prostate Specific Antigen

Abstract: Introduction and Objectives The clinical significance of ductal prostatic carcinoma has not been well defined. We utilized a population-based cancer registry to identify a large group of ductal carcinoma cases to characterize the impact of the ductal subtype on the presentation and survival of men with prostate cancer. Methods A national cancer registry was used to identify incident cases of ductal and acinar adenocarcinomas from 1996–2006. Clinicopathologic variables were analyzed and Cox multivariate survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 23 publications
6
112
4
Order By: Relevance
“…Although the clinical course of DAP remains controversial, the majority of studies indicate that the variant of PCa exhibits more aggressive biological behavior, a more advanced stage, a worse 5-year survival rate and a shorter time to progression compared with conventional acinar carcinoma (4,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clinical course of DAP remains controversial, the majority of studies indicate that the variant of PCa exhibits more aggressive biological behavior, a more advanced stage, a worse 5-year survival rate and a shorter time to progression compared with conventional acinar carcinoma (4,6).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies have clearly confirmed the prostatic origin of DAP, which is supported by a favorable response to orchiectomy, the expression of prostatic-specific antigen (PSA) and ultrastructural findings (3). DAP is a rare subtype of prostate cancer (PCa) that has a poorly-understood etiology, and more commonly occurs in Caucasian males that are >70 years of age (4). A previous study that reviewed the histological slides of 2,600 prostatic carcinomas reported a prevalence of 0.4-0.8% for pure ductal adenocarcinoma and 5% for mixed ductal adenocarcinoma (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is a unique subtype of prostate cancer characterized by the presence of tall, pseudo-stratified, columnar cells with abundant cytoplasm arranged in a papillary pattern (Morgan et al 2010). Serum prostate-specific antigen (PSA) levels are often lower than those of conventional acinar prostate cancer (acinar PCa), and it is often diagnosed at an advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…Ductal adenocarcinoma secretes less prostatic serum antigen (PSA) than acinar adenocarcinoma and it can appear occult on some magnetic resonance imaging (MRI) sequences. 7,8 Most ductal adenocarcinomas arise in the peripheral zone and extend toward the urethral lumen, although occasionally ductal cancer arises in the transition zone exclusively. 3,9 This creates a diagnostic challenge as many ductal cancers present with a normal digital rectal examination and are not detected on routine template TRUSguided biopsy.…”
Section: Introductionmentioning
confidence: 99%